2006
DOI: 10.1159/000091722
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Prefrontal Cortex during the Wisconsin Card Sorting Test as Measured by Multichannel Near-Infrared Spectroscopy

Abstract: Background:The Wisconsin Card Sorting Test (WCST) is a neuropsychological test to evaluate the function of the prefrontal cortex (PFC). However, inconsistent results have been reported concerning whether this task activates the PFC symmetrically or asymmetrically. Objectives:To investigate the brain activation in the PFC during the WCST, we examined blood oxygenation changes of healthy subjects by using multichannel near-infrared spectroscopy (NIRS). Methods:Subjects were 32 healthy volunteers, 18 males and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Because NIRS is noninvasive and does not require fixing of the body as in functional magnetic resonance imaging (fMRI), it is suitable for brain imaging studies in infants and children (22,23). The validity of NIRS has been confirmed by studies on prefrontal function in children (24,25) and by the WCST in adults (26).…”
mentioning
confidence: 99%
“…Because NIRS is noninvasive and does not require fixing of the body as in functional magnetic resonance imaging (fMRI), it is suitable for brain imaging studies in infants and children (22,23). The validity of NIRS has been confirmed by studies on prefrontal function in children (24,25) and by the WCST in adults (26).…”
mentioning
confidence: 99%
“…In previous studies, fOT method has been shown to be sensitive enough for monitoring of physiological blood oxygenation changes during cognitive activation in schizophrenia. [15][16][17] Recently, fOT is being increasingly applied for investigation of prefrontal cortex (PFC) dysfunction in schizophrenia, because the social cognition of schizophrenic patients was associated with PFC activation. PFC dysfunction in individuals with schizophrenia has been detected and evidenced during verbal fluency test (VFT) and other cognitive tests by utilizing fOT.…”
mentioning
confidence: 99%
“…The NIRS technique has several advantages over functional magnetic resonance imaging (fMRI), most notably the lower cost and sensitivity to motion artifacts [8,[30][31][32]. We note, however, that the NIRS detects hemodynamic changes only at the surface of the brain (approximately 3 cm beneath the skull).…”
Section: Advantages and Limitationsmentioning
confidence: 98%
“…Executive function is an assemblage of high-level cognitive domains, including inhibition, working memory, planning, fluency, and shifting, that facilitate the inhibition of incorrect behaviors and the selection of appropriate behaviors according to context and goals [4]. Cognitive shifting is the mental ability to switch between thinking about one concept and begin thinking of another; it is often measured using the Wisconsin Card Sorting Test [5][6][7][8]. Kado et al [6] previously demonstrated that children with ADHD make many more Nelsontype preservative errors (PENs) than do typically developing children (TDC).…”
Section: Introductionmentioning
confidence: 99%